Mystical yet Political: A Liberative Encounter with God through Popular Piety - Espiritu, Wilson Angelo G (Archīum Ateneo, 2020)
Today, an increasing number of Catholics can be found in the countries of the Global South. This coincides with the pontificate of the first pope who comes from that region of the world where the prevalent expression of the Catholic faith is popular piety. Popular piety may be considered as an indispensable phenomenon in Global Catholicism. In his Apostolic Exhortation, Evangelii Gaudium, Pope Francis refers to popular piety as ‘the people’s mysticism’ and calls it a ‘locus theologicus’ which demands attention especially in the contemporary Church’s mission of evangelization. This paper examines popular piety as a probable point of encounter with the liberating grace of God by numerous people in the world. It employs the soteriology of Edward Schillebeeckx, particularly his notion of the interrelationship of mysticism and politics, as a framework for discerning how the liberating grace of God manifests in and through popular piety. This discernment involves identifying liberative qualities of popular piety without the neglect of its oppressive tendencies. It is carefully considered with the awareness that God’s revelation takes place within the finite and broken history of humanity where both grace and sin are interwoven. Thus, it is argued that despite the contrasting presence of liberative and oppressive potentials of popular piety, it can nevertheless be understood as a revelatory sign of God’s saving activity in the here and now. In sum, it is proposed that popular piety has interrelated mystical and political aspects. This model of understanding popular piety does not abandon nor absolutize politics but rather transforms it by strengthening its link to ‘the people’s mysticism’.